A Compact Optical Switch via Plasmonics of Subwavelength Circular‐Sharp Hole Arrays in Metal Films. Issue 3 (13th November 2017) - Sun, Taiming; Deng, Zhixiang; Sheng, Jiabing; Chen, Zhiyong; Zhu, Weihua; Guo, Wei; Wang, Xinlin
Abstract: We studied numerically the enhanced optical transmission (EOT) through periodic subwavelength circular‐sharp hole arrays in metallic films with different edge sharp distribution features of unit structures. Detailed studies indicate that the unit structure edge sharp distribution features strongly influence the surface plasmons (SPs). These results demonstrate that the number of edge sharp activated the localized surface plamons (LSP) resonance on the unit structure is changed by rotating the polarization of the incident light, leading to change the infrared transmittance of the array. Moreover, a compact plasmonic switch via periodic circular‐sharp hole arrays based on the dependence of SPs on unit structural edge sharp distributions is proposed. The finding provides a new idea for designing plasmonics devices, and expands the application range of metal micro‐nano structure in the field of optical communications and information processing. Abstract : In this study, the enhanced optical transmission (EOT) of circular‐sharps shaped hole arrays have been investigated numerically. It is found that the edge sharp distributions have influence the transmission of light mainly by changing the LSP resonance strength on edge sharp. Base on this, a compact plasmonic switch via periodic circular‐sharp hole arrays is proposed. It is turned "on" and "off" state by changing the direction of polarization of the light. This research expand the application range of metal micro‐nano structure in the field of optical communications and information processing.